La Culture Et Son Impact Sur La Performance De L’entreprise: Cas De La Femme Marocaine - Abousaïd Fatima-Zohra; Drissi Selma; Dehbi Sara; Angade Khadija (European Scientific Journal, ESJ, 2017)
More and more women occupy different positions within companies or choose the path of entrepreneurship by running their own business. With their different and complementary qualities to those of their male counterparts, women have been able to contribute effectively to all aspects of the company performance. Nonetheless, women in Morocco still face many cultural impasses in the business sphere, despite all these achievements. Such impasses have indeed a significant impact on the company performance. Thus, this paper challenges that the cultural dimension of the obstacles encountered by women is the most coveted to investigate. Studying this dimension has become a necessity in a context where traditional cultural representations and perceptions still remain deep-rooted in society. The purpose of this article is to list the main cultural barriers the Moroccan women face and the significant impact of such barriers on the company performance. In this regard, this study draws on secondary data, analyzed in conjunction with appropriate texts from the literature about the Moroccan culture. Hence, this paper can be considered as a theoretical start to construct a conceptual model centralizing the main cultural variables inhibiting the emancipation of women in the business sphere.